2011
DOI: 10.1097/bot.0b013e31821b8c28
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Fractures: Epidemiology and Future Projections

Abstract: Periprosthetic fractures are becoming increasingly frequent due to aging population and growing number of total joint replacements involving joints different from hip and knee, such as shoulder and elbow. The treatment of these fractures still represents one of the major challenges for the orthopedic surgeon. Despite all efforts to understand and treat these patients, high rate of failure and mortality are still reported. In this review, the epidemiology of periprosthetic fractures, risk factors and results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(93 citation statements)
references
References 72 publications
5
88
0
Order By: Relevance
“…[6,10,20,21] According to our study, the operation time and amount of bleeding of patients with intraoperative PFF in primary THA were all significantly greater than those of controls, and the financial cost for the treatment of PFF was also considerably higher, especially for those using plate or cortical allograft strut during revision. Besides, PFF posed great challenges to orthopedic surgeons because of its common associations with poor follow-up outcomes and high mortality rate.…”
Section: Discussionmentioning
confidence: 83%
“…[6,10,20,21] According to our study, the operation time and amount of bleeding of patients with intraoperative PFF in primary THA were all significantly greater than those of controls, and the financial cost for the treatment of PFF was also considerably higher, especially for those using plate or cortical allograft strut during revision. Besides, PFF posed great challenges to orthopedic surgeons because of its common associations with poor follow-up outcomes and high mortality rate.…”
Section: Discussionmentioning
confidence: 83%
“…It is an increasingly common procedure, with more than 300,000 primary THRs performed in the US every year [1]. As the number of patients with prosthetic joints in place increases, a growing number of individuals are at risk for implant-related complications, including periprosthetic fracture [2-5]. This particular complication is especially important and clinically relevant because it is typically costly, disabling and morbid.…”
Section: Introductionmentioning
confidence: 99%
“…Periprosthetic fractures of the femur are one of the most severe complications of THA and the number of patients suffering from these injuries will inescapably increase in future years [1,2,23]. Many clinical studies showed devastating outcome results and high complication rates, with hardware failure being one of the most abundant [19,18].…”
Section: Discussionmentioning
confidence: 98%
“…The direct consequence of the worldwide demographic change with a rise of the elderly-but still activepopulation leads to a growing demand for joint arthroplasty in the treatment of osteoarthritis [1,2]. In consequence, the incidence of periprosthetic fractures (PPF) following total hip arthroplasty (THA) is inevitably increasing [3,4].…”
Section: Introductionmentioning
confidence: 99%